Dilemmas in delivering health promotion activities: findings from a qualitative study of mental health nurses in Denmark. Issue 12 (24th December 2020) - Møller, Jane Ege; Møller, Anne; Ledderer, Loni
Abstract : Objective: Recent studies have shown that people with mental illnesses have higher mortality and morbidity rates due to long-term conditions and lifestyle diseases. This knowledge has led to health promotion initiatives in mental health care to improve the physical health of people with mental illness. This article explores how mental health nurses experience working with health promotion activities in mental healthcare practices. Design: We adopted a qualitative research design using an interactive approach. Qualitative content analysis was used to develop the analytical framework. Participants: Focus groups (n=7; n=5) were conducted with two groups of mental health nurses who attended health specialist training sessions in Denmark in the spring and fall of 2018. Results: The findings showed that working with health promotion activities in mental health care created two dilemmas for the mental health nurses: (1) dilemmas related to health promotion that involved discrepancies between the health promotion activities that were offered and patients' autonomy and wishes, and (2) system-related dilemmas stemming from working with screening for risk factors and documentation programmes. The mental health nurses developed different strategies to navigate these dilemmas, such as devising interview techniques for the screening questions and bending guidelines. Conclusions: Mental health nurses found it challenging to implement health promotion activities in mental health care, although they generally found these activities meaningful. The findings show that new health promotion activities need to be adapted to nurses' existing mental healthcare practices; however, this may require some adaptation of existing nursing practices.